Postcoarctectomy syndrome: a contemporary systematic review - Martinez, Hector R.; Salazar-Alejo, Misael; Ballesteros-Suarez, Ana; Perez-Martinez, Luis E.; Moran-Guerrero, Jose A.; Flores-Salcido, Rogelio E.; Jimenez-Franco, Vicente; Britton-Robles, Silvia Cecilia; Benvenutti-Regato, Mario; Figueroa-Sanchez, Jose A. (Frontiers in Surgery, 2025)
Postcoarctectomy syndrome is a serious but poorly understood complication that can occur following surgical or endovascular repair of coarctation of the aorta. This condition presents with severe abdominal pain, persistent hypertension, and gastrointestinal symptoms that can be life-threatening if not promptly recognized and treated. Despite being a known complication for decades, the underlying mechanisms of postcoarctectomy syndrome remain unclear, creating challenges for both early diagnosis and effective treatment. We present the case of a patient with postcoarctectomy syndrome and a systematic review analyzing the clinical presentation, diagnostic approach, and treatment strategies for this complication. We also conduct a systematic literature review, identify key knowledge gaps, and propose future research priorities to address them.